ENHANCING KAZAKHSTAN’S PEACEKEEPING CAPABILITIES: NTEROPERABILITY AND REGIONAL COOPERATION - McDERMOTT, Roger N. (CENTRAL ASIA AND THE CAUCASUS, 2004)
Prior to September 2001, it is fair to say that the principal motivation behind foreign involvement and interest in Central Asia remained strategic and economic, energy; and for the United States its interests were generally secondary and derivative of the interests of others, allies, competitors and commercial actors. Post 11 September and as a result of its commitment to its international, anti-terrorist campaign, however, U.S.relations with the states of Central Asia and its security interests in the region changed dramatically.These states are now on the front lines of the war on terrorism and several states continue to provide critical support to U.S. and allied military forces conducting operations in Afghanistan. The U.S.Military has been much more proactive in the region, recruiting states into the counter terrorist coalition, establishing a presence, and expanding its security cooperation and direct military assistance programs, as well as encouraging several of its al-lies to do the same. More than ten years after independence, many of these states remain unstable and are confronting growing problems with the illegal cross border movement of contraband, armed op-position and terrorist groups, the possible spillover of combat operations from neighboring states, and tension and disputes among neighbors that could escalate. In this environment the local militaries have a valuable function, if properly structured, equipped and trained to confront these types of missions. In most cases the Soviet legacy has hampered in developing needed capabilities more than helped them and they are not adequately prepared. Moreover, it is unlikely that they will be able to responsively make the necessary transition on their own, with-out outside assistance being required. In the post-9/11 world, U.S. and allied formations are operating in several of these states and it programs, as well as encouraging several of its al-lies to do the same. More than ten years after independence, many of these states remain unstable and are confronting growing problems with the illegal cross border movement of contraband, armed opposition and terrorist groups, the possible spillover of combat operations from neighboring states, and tension and disputes among neighbors that could escalate. In this environment the local militaries have a valuable function, if properly structured, equipped and trained to confront these types of missions. In most cases the Soviet legacy has hampered in developing needed capabilities more than helped them and they are not adequately prepared. Moreover, it is unlikely that they will be able to responsively make the necessary transition on their own, with-out outside assistance being required. In the post-9/11 world, U.S. and allied formations are operating in several of these states and it becomes more imperative that the capabilities of these local forces be improved, along with their ability to operate with Western ground and air units.he following analysis charts the course of the varied progress of Kazakhstan’s peacekeeping capabilities, and its focus on interoperability with NATO forces will be considered together with the goal of promoting regional security cooperation.